Cyrtodaria lailae - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
? Capitulum lailae (Gripp, 1927) Fig. 19. Material. — One specimen (ZPAL V.48/22), rostral plates from the upper Paleocene of Fossildalen, Spitsbergen, Svalbard. Measurements. —L, 6.4 mm, W, 4.2 mm. Remarks. —The specimen comprises a single plate (a rostrum) that is likely attributable to? Capitulum lailae (Gripp, 1927), described from the same formation previously by Gripp (1927) and redescribed and refigured by Withers 1953: 112–114, pl. 4.1–4.11), who compared this taxon to Mitella mitella (Linnaeus, 1758) and placed the species in Mitella Oken, 1815, with reservations. However, M. mitella is currently assigned to Capitulum (e.g., Chan et al. 2009), hence the provisional placement of? C. lailae in that genus. Barnacles have rarely been reported from ancient cold seep-associated deposits so its presence in the Basilika Formation merits a note. Stratigraphic and geographic range. —Upper Paleocene cold seep carbonates from the Basilika Formation, Fossildalen, Spitsbergen, Svalbard. Published as part of Hryniewicz, Krzysztof, Amano, Kazutaka, Bitner, Maria Aleksandra, Hagström, Jonas, Kiel, Steffen, Klompmaker, Adiël A., Mörs, Thomas, Robins, Cristina M. & Kaim, Andrzej, 2019, A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard, pp. 101-141 in Acta Palaeontologica Polonica 64 (1) on page 124, DOI:10.4202/app.00554.2018, http://zenodo.org/record/10980900